Dynamic modeling of spatial-temporal characteristics of dust in south and southeastern Iran with REG-CM4 model - Motahhareh Zargari; Mahdi Boroughani; Alireza Entezari; Abbas Mofidi; Mohammad Baaghideh (تحقیقات کاربردی علوم جغرافیایی)
The aim of the present study is to dynamically model the spatial-temporal characteristics of dust in the south and southeast of Iran with REG-CM4 model using monthly dust data and RegCM4 data. For this purpose, the dust distribution of the IDW method along with the dust diagrams were plotted. The RegCM4 model was implemented with the paired Lambert image imaging system for 40 km horizontal separation with the paired chemistry model. The location of monthly and annual dust distribution shows the highest amounts of dust for the cities of Zabol, Bandar Abbas, Zahedan and Jask compared to Sirjan, Kahnooj and Lar stations. The highest frequency of dust in Sistan and Baluchestan (48%), Hormozgan (27%) and Fars provinces with 16% and the lowest frequency for Kerman province (9%). In general, the summer seasons (at Sistan station) and the winter (Kerman station) have the highest and minimum dust events, respectively. The time survey also has the highest amount of dust for the warm months of the year and the lowest for the cold months of the year. July at Zabol station and November and December at Sirjan station have the highest and lowest dust levels, respectively. The RegCM4 climate model also shows maximum dust on the southeast, south and south coasts for different variables.